Supervision of the Regional House of Representatives (DPRD) on Regional Head Policies in the Perspective of Checks and Balances in Konawe Regency - Hasjad Hasjad (Jurnal Restorasi : Hukum dan Politik, 2026)
This study aims to analyze the implementation of the supervisory function of the Regional People's Representative Council (DPRD) on the policies of Regional Heads in the perspective of the principle of checks and balances in Konawe Regency. In the local government system based on Law Number 23 of 2014 concerning Regional Government, the DPRD has the functions of legislation, budget, and supervision as a manifestation of the power balancing mechanism at the local level. However, in practice, the effectiveness of DPRD supervision often faces various obstacles, both normative and political. This research uses normative-empirical legal research methods with a legislative approach and a conceptual approach, and is supported by field data through interviews and documentation. The results of the study show that the supervision of the DPRD in Konawe Regency has been carried out through the mechanism of working meetings, the right of interpellation, the right of inquiry, and the right to express opinions, but it is not fully optimal in realizing the balance of power. Political relations factors, limited institutional capacity, and lack of policy transparency are the main obstacles in the implementation of the supervisory function. From the perspective of checks and balances, it is necessary to strengthen the institutional capacity of the DPRD, increase public participation, and political ethics commitment to ensure the creation of accountable and democratic local governance. Thus, the supervision of the DPRD is not only formal-procedural, but also substantive in maintaining the balance of power in the regions.